Straddling Federal/Provincial Government Relations: The Work of Adult Additional Language Education for Immigrants’ Employment Integration - Tara Gibb (Adult Education Research Conference, 2011)
This paper discusses some early findings from research examining the implementation of adult English-as-an-Additional Language (EAL) education policy in Canada. It examines the challenges adult language educators and language researchers encounter during the implementation of an initiative that straddles two levels of government in the Canadian federal system and is intended to assist new immigrants with settlement and employment integration.
Keywords: federal and provincial policy; English-as-an-Additional Language education; immigration